Exploring maintainability and performance in Ballerina Microservices - Alves, André Filipe Ribeiro (2023)
Microservices architecture currently is the industry norm for creating applications since it allows teams to focus on individual services related to specific business functionalities, reducing the overall application complexity and improving its maintainability. However, microservices architecture has liabilities regarding service integration, communication, governance, and data management. To solve these liabilities, the industry and academic community have focused on creating new frameworks and solutions. More recently, the focus changed to creating new programming languages focused on microservices. This study aims to investigate the effects of language-oriented approaches in developing microservices. The work focuses on Ballerina, a programming language created to simplify the creation and integration of microservices. From the literature’s analysis, Ballerina demonstrates the ability to be more beneficial than the most common implementations of microservices that use more common frameworks. To further investigate these statements, an experience based on the migration of existing microservices developed in Java with the use of the framework Spring Boot was conducted. This experience used a migration strategy created based on the language’s specificities. The resulting Ballerina microservice is compared with its original counterpart. The experience focused on analyzing both solutions in terms of maintainability and performance. Therefore, the Goals, Questions, Metrics (GQM) approach was used to obtain metrics for the mentioned quality attributes. From the obtained results, it was concluded that the Ballerina solution presents differences from the Spring Boot solution, being superior regarding maintainability and inferior in performance.